Approaches, tools and methods used for setting priorities in health research in the 21 st century - Sachiyo Yoshida (Edinburgh University Global Health Society, 2016)
Health research is difficult to prioritize, because the number of possible competing ideas for research is large, the outcome of research is inherently uncertain, and the impact of research is difficult to predict and measure. A systematic and transparent process to assist policy makers and research funding agencies in making investment decisions is a permanent need.